A survey of fungi and mycotoxins in food in the rural homes of Limpopo Province - Phillice, Mamphuli Azwifaneli (2008)
Maize (Zea mays L.) is an important cereal world-wide, serving as seed for growers, food for man and livestock as well as an industrial raw material. Unfortunately, it is also a suitable substrate for growth, development and activity of spoilage fungi. Fungal growth is a major problem in cereal grains throughout the world and may lead to poor quality of the products, as well as adverse effects to human and animal health due to mycotoxin production. Maize is usually harvested at high moisture content and then dried to bring down the moisture content to a safe level before storage. Delay in drying to safe moisture levels increases risks of mould growth and mycotoxin production. In rural villages maize is dried using only sun drying and they rely on sacks, thatched silo and drums as their storage facilities. This is insufficient to prevent damage by insects, rain, and rodents, which in turn allows fungi to invade these storage facilities. Maize was sampled in two rural areas of Venda (Limpopo Province) and the percentage moisture content was determined and then screened for total fungal contamination. The samples were also analysed for mycotoxins that have been reported to commonly occur in maize. There was no significant difference in the extent of fungal contamination in Mapate and Folovhodwe villages. Of the fungal species detected, Aspergillus species were the most common with Aspergillus flavus being the most predominant. On analysis by the multi-mycotoxin screen, aflatoxin had the highest incidence amongst mycotoxin, followed by T-2 toxin. However on using the VICAM method of analysis aflatoxins, deoxynivalenol and fumonisin were the most predominant mycotoxins in the samples, while zearalenone toxin was also amongst predominant mycotoxins but with the highest level of 0.1 ppm. Most of the mycotoxin-containing extracts were found to reduce the % cell viability of human lymphocytes, after 24 hours of incubation as determined by the methyl thiazole tetrazolium salt assay. vii In conclusion the co-occurrence of these toxins in maize and maize meal may highlight the problems associated with the intake of numerous toxins that could in turn lead to more adverse health effects such as liver, oesophageal, breast and cervical cancer, male reproductive tract damage and gynacomastasia. There is, therefore, need to disseminate information to these people, using simplified methods such as programs on radio and televisions on mycotoxin hazards and discussion on the issue should also feature regularly on daily newspapers and magazines, about the dangers and management aspects of mycotoxins, and the susceptible produce. === Prof. M. F. Dutton Mr. F. E. van Zyl